A review article on biosimilar infliximab SB2 in the treatment of rheumatoid arthritis. (November 2017) - Bellinvia, Salvatore; Ashraf, Madiha; Polosa, Riccardo; Edwards, Christopher
TNF inhibition has had a major impact as an approach for treating rheumatoid arthritis and a series of biologic agents directed against TNF have been developed for clinical use. Infliximab, a chimeric monoclonal antibody against soluble and membrane-bound TNF-α, was the biopharmaceutical to lead this 'biologics revolution'. However, with expiration of patent protection of the originator medicinal product, biosimilar versions of infliximab have been developed through biosimilarity studies and randomized controlled trials aiming to assess pharmacokinetic, pharmacodynamic and clinical equivalence to their originator (reference product) in patients with moderate-to-severe disease activity. This review summarizes the clinical development of SB2, a biosimilar of infliximab, in rheumatoid arthritis.